ADAPTATION OF DIGITAL PAYMENT TECHNOLOGY: THE USE OF QRIS IN THE SOCIAL TRANSFORMATION OF KAYUTANGAN VILLAGE MALANG - Musfiah Saidah; Shafira Zahra Ramadhani; Lulu Ulrojabiah (Program Studi Pengembangan Masyarakat Islam (PMI) FDIKOM, UIN Syarif Hidayatullah Jakarta, 2026)
In the digital era, the use of technology greatly influences human life systems, including patterns of social interaction and community empowerment. It encourages the formation of agents of socialchange who utilize digital technology ethically and strategically to empower communities. Technology is a key element in today's digital ecosystem, significantly impacting social transformation. Within this framework, digital transformation in the village tourism sector is crucial for supporting local economic sustainability. However, the technology adoption process is not always linear and orderly among business actors. This study examines the perceptions, motivations, obstacles, and strategies developed by actors in their daily lives when managing a culture-based tourism village. The aim is to understand the community's personal experiences in adopting technology to promote, develop, and conduct QRIS-based digital payments in Kayu Tangan Heritage Village, Malang City. This study uses a qualitative phenomenological approach to understand lived experiences and their meanings. It involved four informants two traders, one gatekeeper resident, and one expert. Data were collected through in-depth interviews and analyzed using thematic analysis, including coding and identifying key patterns. This study is unique in offering a micro-level perspective on how local communities adapt to technological change, contributing to global insights on grassroots digital transformation. The results indicate that the technology adaptation process is gradual and uneven among actors. Acceptance of QRIS is influenced by several factors, such as initial understanding of the technology through socialization, the role of local actors, perceptions of its benefits, and experience in conducting transactions. This study concludes that technology adaptation in heritage villages is not simply a technical issue, but a social process influenced by relationships, experiences, and how actors interpret the technology. These findings underscore the importance of a participatory and contextual approach in driving inclusive digital transformation in culture-based tourism areas.